Digital Transformation in Education aligned with the DigCompEdu Framework (Journal of Parents and Teachers, 2023)
The technological transformation that is taking place at the present time, together with the implementation of European reference frameworks for teachers, has highlighted the right and the need for digital training in this sector. These pages show the importance of teachers incorporating digital competence both intrinsically and in educational settings. Finally, a prospective of digital technologies in education is carried out taking into account the recent transcendental changes in all areas of society.
Keywords: information and communication technologies; teacher training; European Community; primary education; technologic education